A Phase I Evaluation of Inactivated Influenza A/H5N1 Vaccine Administered by the Intradermal or the Intramuscular Route - Patel, Shital M. (2009)
In a phase I clinical trial, one hundred healthy young adults were randomized to receive two doses 28 days apart of an inactivated, subvirion vaccine containing 15µg or 45µg of influenza A/H5N1 hemagglutinin (HA) by the intramuscular (IM) route, or 3µg or 9µg of H5 HA by the intradermal(ID) route. Seventy-seven subjects received a third dose. All regimens were safe and well tolerated. Antibody responses after two or three doses were low (≤20% or ≤38%, respectively) and similar in groups given 3µg or 9µg ID or 15µg IM, and were significantly lower than those given 45µg IM. Higher dosages of H5 HA and/or inclusion of adjuvant will be required to enhance immunogenicity by the ID route.